Sustainability Awareness of In-Service Physical Education Teachers - Salvador Baena-Morales; Alberto Ferriz-Valero; Javier Campillo-Sánchez; Sixto González-Víllora (MDPI AG, 2021)
Physical Education has been described as a subject with unique characteristics that can contribute to achieving Sustainable Development Goals. However, an analysis of PE teachers' (PETs) sustainability consciousness has not yet been conducted. For this purpose, a total of 203 PETs completed the validated SCQ-S instrument to measure the three dimensions of sustainable development in three components of consciousness (attitudes, knowledge and behaviours). The results obtained show that the PETs have a high consciousness for sustainable development (SD), except for attitudes within the economic dimension. Sex has been identified as a variable that determines awareness in sustainability with significantly higher scores for women in all the variables evaluated, except for knowledge and behaviour in the social dimension. These findings provide new knowledge within the Physical Education and SD paradigm, serving as a link for future research that aims to harness the benefits of Physical Education for the sustainability of the planet.